PIJAT EFFLEURAGE PADA NYONYA WDALAM ASUHAN KEBIDANAN MASA KEHAMILAN DI KLINIK PRATAMA WIDURI SLEMAN - Nadia Faradilla; Eny Retna Ambarwati (Husada Mahakam, 2021)
Background: Physiological adaptation to the musculoskeletal system is one of the changes that are often complained of by pregnant women, namely changes in posture, especially in the third trimester of pregnancy. There are 60-80% of pregnant women in various regions of Indonesia who experience back pain (back pain) in their pregnancy. The midwife's efforts to improve services in accordance with the professional code of ethics, midwives began to develop complementary therapeutic innovations in Indonesia. One of the complementary therapies that are often used to reduce back pain during pregnancy is effleurage massage. Objectives: To apply effleurage massage to reduce back pain in obstetric care during pregnancy in Ny. W at the Primeric Widuri Sleman Clinic. Method: This research uses descriptive analytic method, by describing the facts of the study obtained from interviews and direct observations on Mrs. W by involving the respondent's husband for 7 days conducted in October 2019. Results: After effleurage massage was done on Mrs. W, for 10-15 minutes a day, there was a change in Ny W from moderate pain to mild pain, from pain scale number 6 to number 3. Conclusion: Effleurage massage is effective for reducing back pain in pregnant women in the third trimester at the Primeric Widuri Sleman Clinic Keywords: Pregnancy Care, Back Pain, Effleurage Massage